Geodiversity, Heritage, and Geoethics in an Archipelago - Rojas Consuegra, Reinaldo; Mengana, Jorge Isaac; Cárdenas Ortiz, Rolando Pedro; Nuñez Cambra, Kenya E.; Pérez Díaz, Noel; Martín González, Osmel (Springer, 2018)
The Cuban archipelago has an extremely complex geology. In this chapter, an overview on its peculiarities is given. It is also presented a historical sketch of the Cuban geological heritage, and the current menaces to preserve it. Then, the current Cuban policy and practical efforts for geoconservation are described.
Keywords: Geological Heritage; Geopark; Chicxulub impact; Loma Capiro; Earth and Environmental Science; Geoethics; Cuba